Spontaneous CP violation in the 3-3-1 model with right-handed neutrinos - Doff, A.; de S. Pires, C. A.; Rodrigues da Silva, S. (American Physical Soc, 2006)
We implement the mechanism of spontaneous CP violation in the 3-3-1 model with right-handed neutrinos and recognize their sources of CP violation. Our main result is that the mechanism works already in the minimal version of the model and new sources of CP violation emerges as an effect of new physics at energies higher than the electroweak scale.